Building a community of practice around a community of inquiry: an examination of EFL students' perceptions of a virtual internship - Nouf J. Aljohani; Khulod Aljehani (Springer, 2024)
Abstract In response to the new policy of English department, the internship program has been shifted to virtual programmes. As part of this initiative, the university has collaborated with other educational sectors to offer a virtual English as a Foreign Language (EFL) internship programme aimed at training individuals as EFL teachers. The aim of the study was to investigate student perceptions of dynamic social structures and communities of practice in technologically mediated environments, particularly in relation to virtual internships. The authors recognised a gap in research regarding how EFL students create meaningful learning experiences and how they build their practical knowledge in mediated communication environments. Quantitative and qualitative research methods were used. 50 students comprised the study subjects. The data were collected from multiple sources: interviews, students' reflections, and community of inquiry and practice survey instruments. The findings revealed that an unprepared virtual environment led to social anxiety and challenges related to real-world work experience. The study suggests that evidence-based interventions in technologically mediated, virtual learning environments can help to resolve study findings with this goal: fostering a sense of belongingness and community that can promote effective remote interactions between learners and their teachers to ensure that internships serve students best.